Time-Resolved Determination of the CcpA Regulon of Lactococcus lactis subsp. cremoris MG1363 - Zomer, Aldert L. (American Society for Microbiology, 2007)
Carbon catabolite control protein A (CcpA) is the main regulator involved in carbon catabolite repression in gram-positive bacteria. Time series gene expression analyses of Lactococcus lactis MG1363 and L. lactis MG1363ΔccpA using DNA microarrays were used to define the CcpA regulon of L. lactis. Based on a comparison of the transcriptome data with putative CcpA binding motifs (cre sites) in promoter sequences in the genome of L. lactis, 82 direct targets of CcpA were predicted. The main differences in time-dependent expression of CcpA-regulated genes were differences between the exponential and transition growth phases. Large effects were observed for carbon and nitrogen metabolic genes in the exponential growth phase. Effects on nucleotide metabolism genes were observed primarily in the transition phase. Analysis of the positions of putative cre sites revealed that there is a link between either repression or activation and the location of the cre site within the promoter region. Activation was observed when putative cre sites were located upstream of the hexameric −35 sequence at an average position of −56.5 or further upstream with decrements of 10.5 bp. Repression was observed when the cre site was located in or downstream of putative −35 and −10 sequences. The highest level of repression was observed when the cre site was present at a defined side of the DNA helix relative to the canonical −10 sequence. Gel retardation experiments, Northern blotting, and enzyme assays showed that CcpA represses its own expression and activates the expression of the divergently oriented prolidase-encoding pepQ gene, which constitutes a link between regulation of carbon metabolism and regulation of nitrogen metabolism.